Frost-Heaved Bedrock Features: A Valuable Permafrost Indicator - Dionne, Jean-Claude (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1983)
ABSTRACTFrost-heaved bedrock features are periglacial forms produced by the vertical displacement of bedrock fragments. Blocks, frost-wedged from bare bedrock along joints, are raised above the general surface by heave. Although mentioned in the literature of the late 19th century, they have been described and studied in detail only recently. They are widespread in the northern hemisphere, notably in Canada, Greenland and Spitsbergen, where they develop in lithologies with well-developed systems of joints. Commonly, heaved blocks exhibit weathered and lichen-covered surfaces except at their base where freshly exposed rock indicates recent heaving. They result from frost processes, particularly from wedging and heaving due to pressure of the freezing of free-water in joints. Active and most non-active features are located in permafrost regions. The southermost occurrence in the northern hemisphere is the Groulx Mountains, in Québec (51°45'N, alt. 1000 m). The mean annual air temperature for the area of best-developed features ranges from -4° to -100C, with the number of days of frost ranging from 178 to 300. A thin snow cover is common to most sites. Based on climatic data and on the geographical distribution of frost-heaved bedrock features, it is suggested that permafrost occurrence is obvious. Relict features found outside the present-day permafrost zones should indicate former permafrost conditions.